Contracts as the Main Legal Basis in Islamic Economic Disputes: A Juridical-Empirical Study of Lawlessness in Religious Courts - Chandra Chandra; Beni Ahmad Saebani; Ija Suntana; Hasan Bisri (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
Despite the growing body of literature on Islamic economic dispute resolution, no study has systematically reconstructed the conceptual boundary between unlawful acts (perbuatan melawan hukum) and contractual default (wanprestasi) within the framework of sharia contract law. This gap produces legal inconsistency and undermines substantive justice in Indonesian Religious Courts. This study critically examines and reconceptualizes the application of unlawful act doctrine in sharia economic disputes, proposing a contract-centered legal reasoning model integrated with maqāṣid al-sharī'ah as a normative corrective framework. A juridical-empirical approach with qualitative case study design was employed. Data were drawn from Religious Court decisions on sharia economic disputes, supplemented by in-depth interviews with judicial officials and systematic documentary analysis of the Compilation of Sharia Economic Law (KHES) and DSN-MUI fatwas. Inductive thematic analysis followed the Miles and Huberman interactive model, with source and method triangulation to ensure validity. Judges consistently accepted unlawful act claims in contract-originated disputes without adequately examining the contractual structure as the primary legal foundation. References to KHES and DSN-MUI fatwas were marginal and non-systemic, resulting in significant inter-decision inconsistency across cases with substantively similar fact patterns. Practical flexibility in evidentiary standards emerged as a key driver of this misqualification. This study is the first to offer a conceptual reconstruction of unlawful act doctrine within sharia economic dispute law by positioning the contract as the primary analytical anchor and unlawful acts as a residual legal regime, applicable only when the disputed conduct falls entirely outside the contractual relationship. Unlike prior work focused on institutional or procedural dimensions, this study integrates modern contract law theory, socio-legal analysis, and maqāṣid al-sharī'ah into a coherent normative framework for religious court adjudication. The findings provide actionable guidance for judges, policymakers, and the Supreme Court in developing interpretive standards that strengthen legal certainty and sharia compliance in Islamic economic justice